Friend or foe? - Louis J. Kotzé; Louise Du Toit; Duncan French (Oñati Socio-Legal Series)
In this paper, we focus on the structural complicity of international environmental law (IEL) in causing and exacerbating climate injustices. We aim to show that although the intentions behind IEL may be well-meaning, it often inadvertently, but also deliberately at times, plays a role in creating, sustaining and exacerbating the many paradigms that drive climate injustice in the Anthropocene. We focus on three aspects: IEL’s neoliberal anthropocentrism; its entanglement with (neo)colonialism; and its entrenchment of the sovereign right to exploit energy resources. We conclude with a call for thoroughgoing, and urgent, reform of IEL.